2023
DOI: 10.1038/s41392-023-01311-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of metabolomics in urolithiasis: the discovery and usage of succinate

Abstract: Urinary stone is conceptualized as a chronic metabolic disorder punctuated by symptomatic stone events. It has been shown that the occurrence of calcium oxalate monohydrate (COM) during stone formation is regulated by crystal growth modifiers. Although crystallization inhibitors have been recognized as a therapeutic modality for decades, limited progress has been made in the discovery of effective modifiers to intervene with stone disease. In this study, we have used metabolomics technologies, a powerful appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Aggregation of A β peptide is commonly believed to be central to the induction of AD, but the mechanism of toxicity is still unclear [38] . The intensely studied nematode worm C. elegans can be transgenically engineered to express human A β .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation of A β peptide is commonly believed to be central to the induction of AD, but the mechanism of toxicity is still unclear [38] . The intensely studied nematode worm C. elegans can be transgenically engineered to express human A β .…”
Section: Resultsmentioning
confidence: 99%
“…Aggregation of Aβ peptide is commonly believed to be central to the induction of AD, but the mechanism of toxicity is still unclear. [38] The intensely studied nematode worm C. elegans can be transgenically engineered to express human Aβ. Depending on the timing of Aβ expression, these worms can have measurable phenotypes that functions as a read-out of Aβ toxicity.…”
Section: Aβ Aggregation Assay In Transgenic C Elegansmentioning
confidence: 99%
“…Moreover, studying the metabolome could provide clues to systemic or intrarenal differences that influence unrecognized steps in kidney stone pathogenesis. A metabolomics approach can be used to investigate the serum and urine of patients with kidney stones, with the aim of discovering abnormal metabolic pathways involved in urolithiasis and identifying novel markers for the diagnosis of kidney diseases associated with this condition [62]. A recent study evaluated the metabolite profiles of serum from children with urolithiasis and normal controls using ultra-performance liquid chromatography-mass spectrometry [63].…”
Section: Discussionmentioning
confidence: 99%
“…Vinaiphat and colleagues demonstrated that PMCA2 acts as a receptor for COM crystals and is involved in crystal adhesion 143 . Zhang and colleagues reported that succinate can inhibit crystal adhesion, thus preventing stone formation 144 . Mulay and colleagues discovered that TNFR signalling actively contributed to the initiation of CaOx crystal adhesion, and blocking TNFR therapeutically may slow down the process of stone formation 145 .…”
Section: The Forming Processes Of Calcified Aggregates In Renal Tubul...mentioning
confidence: 99%